The NOD2insC polymorphism is associated with worse outcome following ileal pouch-anal anastomosis for ulcerative colitis. Issue 10 (9th August 2012) - Tyler, Andrea D; Milgrom, Raquel; Stempak, Joanne M; Xu, Wei; Brumell, John Hunter; Muise, Aleixo M; Sehgal, Rishabh; Cohen, Zane; Koltun, Walter; Shen, Bo; Silverberg, Mark S
Abstract : Background: Inflammatory complications after ileal pouch-anal anastomosis (IPAA) for ulcerative colitis (UC) are common. Objective: To investigate whether genetic factors are associated with adverse pouch outcomes such as chronic pouchitis (CP) and a Crohn's disease-like (CDL) phenotype. Design: 866 patients were recruited from three centres in North America: Mount Sinai Hospital (Toronto, Ontario, Canada), the Cleveland Clinic (Cleveland, Ohio, USA) and Penn State Milton S Hershey Medical Center (Hershey, Pennsylvania, USA). DNA and clinical and demographic information were collected. Subjects were classified into post-surgical outcome groups: no chronic pouchitis (NCP), CP and CDL phenotype. Results: Clinical and genetic data were available on 714 individuals. 487 (68.2%) were classified as NCP, 118 (16.5%) CP and 109 (15.3%) CDL. The presence of arthritis or arthropathy (p=0.02), primary sclerosing cholangitis (p=0.009) and duration of time from ileostomy closure to recruitment (p=0.001) were significantly associated with outcome. The NOD2 insC (rs2066847) risk variant was the single nucleotide polymorphism (SNP) most significantly associated with pouch outcome (p=7.4×10 −5 ). Specifically, it was associated with both CP and CDL in comparison with NCP (OR=3.2 and 4.3, respectively). Additionally, SNPs in NOX3 (rs6557421, rs12661812), DAGLB (rs836518) and NCF4 (rs8137602) were shown to be associated with pouch outcome with slightly weaker effects. A multivariable risk model combining previously identified clinical (smoking status, family history of inflammatory bowel disease), serological (anti- Saccharomyces cerevisiae antibody IgG, perinuclear antineutrophil cytoplasmic antibody and anti-CBir1) and genetic markers was constructed and resulted in an OR of 2.72 (p=8.89×10 −7 ) for NCP versus CP/CDL and 3.22 (p=4.11×10 −8 ) for NCP versus CDL, respectively. Conclusion: Genetic polymorphisms, in particular, the NOD2 insC risk allele, are associated with chronic inflammatory pouch outcomes among patients with UC and IPAA.